2011
DOI: 10.1074/jbc.m111.259101
|View full text |Cite
|
Sign up to set email alerts
|

Rod Phosphodiesterase-6 (PDE6) Catalytic Subunits Restore Cone Function in a Mouse Model Lacking Cone PDE6 Catalytic Subunit

Abstract: Rod and cone photoreceptor neurons utilize discrete PDE6 enzymes that are crucial for phototransduction. Rod PDE6 is composed of heterodimeric catalytic subunits (␣␤), while the catalytic core of cone PDE6 (␣) is a homodimer. It is not known if variations between PDE6 subunits preclude rod PDE6 catalytic subunits from coupling to the cone phototransduction pathway. To study this issue, we generated a cone-dominated mouse model lacking cone PDE6 (Nrl ؊/؊ cpfl1). In this animal model, using several independent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…ERG measurements of Nrl Ϫ/Ϫ / cpfl1 double mutants lacked, as expected, rod activity, but surprisingly showed S-cone-mediated responses under light-adapted conditions. Moreover, immunoblotting of Nrl Ϫ/Ϫ /cpfl1 retinae revealed the presence of cone PDE6H and rod PDE6G suggesting that the PDE6G protein is normally expressed in murine cones (70). In addition to the inhibitory PDE6 proteins, catalytic rod PDE6 subunits were detectable in cone photoreceptors of the all cone-like retina model.…”
Section: Discussionmentioning
confidence: 93%
“…ERG measurements of Nrl Ϫ/Ϫ / cpfl1 double mutants lacked, as expected, rod activity, but surprisingly showed S-cone-mediated responses under light-adapted conditions. Moreover, immunoblotting of Nrl Ϫ/Ϫ /cpfl1 retinae revealed the presence of cone PDE6H and rod PDE6G suggesting that the PDE6G protein is normally expressed in murine cones (70). In addition to the inhibitory PDE6 proteins, catalytic rod PDE6 subunits were detectable in cone photoreceptors of the all cone-like retina model.…”
Section: Discussionmentioning
confidence: 93%
“…It has been recently demonstrated that cones in Nrl À/À ;Cpfl1 mice also express rod PDE6 catalytic subunits that can partially replace the nonfunctional cone PDE alpha subunit. 31 Potentially, this may also reduce toxic cGMP levels and support cone viability and function in R91W;Nrl À/À ;Cpfl1 mice. To completely ablate retinal function and potentially accelerate degeneration, we generated quadruple R91W;Nrl À/À ;Cpfl1;rd10 mice, which carry an additional mutation in the beta subunit of rod PDE6.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently an elegant study in a mouse model lacking cone Pde6c showed that cones expressed the rod photoreceptor Pde6a/b subunit proteins and that these subunits were used instead for cone phototransduction. 32 Therefore, the expression of rod phototransduction genes in FACS Tg(TaC-P:EGFP) wild-type and mutant cones was examined. We found that wild-type cones expressed very low levels of pde6a and pde6b, whereas mutant cones had highly upregulated levels of these two genes at both 4 and 7 d.p.f.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in a genetically derived all-cone retina mouse model lacking cone Pde6c (Nrl À / À ;cpfl1), it was demonstrated that the cones instead expressed the rod Pde6 catalytic subunits conferring phototransduction capability to the cones. 32 Similarly, in the rd10 mouse (which lacks the rod Pde6b gene), the cone Pde6a 0 subunit was transgenically expressed in the mutant rd10 rods and this rescued the response to light, demonstrating that cone Pde6a 0 can functionally substitute for Pde6ab. 38 These studies suggest that the rod and cone Pde6 catalytic subunits can functionally substitute for one another and our work further implies that the local environment can determine rod and cone coupling.…”
Section: Discussionmentioning
confidence: 99%